Pengaruh Penerapan Absensi Fingerprint dan Motivasi Kerja terhadap Disiplin Kerja Pegawai pada MAN 3 Bener Meriah Kabupaten Bener Meriah - Syarifudin Syarifudin; Sabri Sabri; Erna Erna; Masri Ramadhan; Rahmita Dini (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study was to measure the effect of fingerprint attendance and work motivation on employee work discipline at Man 3 Bener Meriah. The number of respondents in the study was 45 people using saturated sampling techniques. The data collected through the questionnaire were expressed in the form of a Likert scale, then tabulated and processed using multiple linear regression techniques using the SPSS version 27 application. The results of the multiple linear regression equation Y = 2.507 + 0.583 + 0.422, indicate that there is a partial effect of fingerprint attendance on employee work discipline with a significance level of 0.000 <0.05 with a t-count value of 4.316, there is also a partial effect of work motivation on employee work discipline with a significance level of 0.002 <0.05 with a t-count value of 3.252. The results of the study also showed an influence between fingerprint attendance and work motivation simultaneously on the work discipline of Man 3 Bener Meriah employees with a significance level of 0.000 <0.05 with a calculated f value of 14,634. The R square Determinant Coefficient shows a figure of 0.411, this means that the work discipline variable is influenced by the fingerprint attendance variable and work motivation by 41.1% and 58.9% is influenced by other variables not examined in this study.